PENGUNGSI, KONSTITUSI: NALAR DISKURSIF HUKUM - Marluwi Marluwi (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
Social conflict engenders refuges. There must be a law or a rule to manage refuges. It is aimed at protecting every citizen rights as written in preamble of UUD 1945: “Bahwa sesungguhnya kemerdekaan itu ialah hak segala bangsa dan oleh sebabitu, maka penjajahan di atas dunia harus dihapuskan karena tidak sesuai dengan perikemanusiaan dan perikeadilan”. Pancasila, UUD 1945, act number 39, year of 1999 about human rights and act number 40, year of 2008 about annulment of races and ethnics discrimination arefour foundations that should be the basis of regulation to protect refuges rights as victims of social conflict.